The Sense of Commitment: A Minimal Approach - Michael, John; Sebanz, Natalie; Knoblich, Günther (Frontiers in Psychology, 2016)
This paper provides a starting point for psychological research on the sense of commitment within the context of joint action. We begin by formulating three desiderata: to illuminate the motivational factors that lead agents to feel and act committed, to pick out the cognitive processes and situational factors that lead agents to sense that implicit commitments are in place, and to illuminate the development of an understanding of commitment in ontogeny. In order to satisfy these three desiderata, we propose a minimal framework, the core of which is an analysis of the minimal structure of situations which can elicit a sense of commitment. We then propose a way of conceptualizing and operationalizing the sense of commitment, and discuss cognitive and motivational processes which may underpin the sense of commitment.